Epidemiological monitoring of ticks in public woods in a risk area for Brazilian Spotted Fever - Brites-Neto, José (2014)
The importance of Brazilian Spotted Fever (BSF) increased significantly by the increasing ratio of cases and deaths diagnosed and high mortality rate in São Paulo between 2000 and 2009, exacerbated by the expansion of the transmission areas, with modification on ecological and epidemiological characteristics and the occurrence of cases in urban and suburban areas. This paper presents results of monitoring a public forest in the city of Americana/ SP where, in the absence of amplifying hosts of rickettsia (capybara) through established control and after two years of monitoring by acarological research, changed the epidemiological status of the area infested by ticks and epidemiological risk for BSF to non-infested area and free for human frequency, with the nullity of human parasitism by Amblyomma cajennense and Amblyomma dubitatum.